Kreativitas Menggambar Dekoratif Tampah Pada Muatan Pembelajaran Seni Rupa Kelas IV SD Negeri 103 Kota Bengkulu - Sesilia; Anggraini, Dwi; Kurniawati, Ike (JURIDIKDAS, 2025)
The purpose of this study was to describe students' creativity in the process of drawing decorative trays on the content of fine arts learning for grade IV of SD Negeri 103 Kota Bengkulu. The type of research is descriptive qualitative, the subjects of the research were grade IV students who were divided into 4 groups. Data collection used observation, interviews, and documentation, followed by data analysis through the stages of data reduction, data display, and verification. The results of the study showed that students' creativity emerged in the aspect of curiosity, they asked about the use of tools and materials, sketches, and forms of tray media. Students also showed creativity by appreciating the work of other groups. Then the imaginative aspect, students' creativity emerged in the process of drawing sketches, where the images made were the result of their own ideas, they did not ask other groups to see existing examples. At the finishing stage, the groups gave each other compliments, they also displayed and stored their work well. However, students' creativity has not emerged in the imaginative aspect and dared to take risks, in the basic and detailed coloring process, students have not tried to mix various colors to draw. Students tend to be less willing to take risks, only drawing simple and familiar objects. At the finishing and drying stage, students also have not shown the courage to change or repair parts that are less suitable.